Optimasi Sifat Kekerasan dan Struktur Mikro Paduan Aluminium Silikon A383 dengan Variasi Perlakuan Panas - Paipinan, Paipinan Batara Randa; Ahmad Zubair Sultan; Muhammad Arsyad Suyuti (Politeknik Negeri Ujung Pandang, 2026)
The purpose of this study was to determine the effect of heat treatment on the hardness and microstructure of A383 aluminum alloy. The research method includes materials, tools, and experimental procedures carried out during the study. The tested material was A383 aluminum alloy in the form of a cylindrical block, which was machined into test specimens with dimensions of 10 × 10 × 10 mm. The heat treatment process was conducted in two stages. In the first stage, the specimens were subjected to solution heat treatment at a temperature of 550 °C with a holding time of 2 hours followed by quenching in water media. In the second stage, the specimens were subjected to artificial aging at temperatures of 150 °C, 200 °C, and 250 °C with holding times of 4, 5, and 6 hours. The tests carried out included chemical composition testing, Brinell hardness testing, and microstructure observation. The results show that the hardness of A383 aluminum alloy can be improved through a sequence of solution heat treatment, quenching, and artificial aging processes. The maximum hardness value of 112.86 HB was obtained at an aging temperature of 200 °C with a holding time of 4 hours. Microstructure observations indicate that the peak aging condition produces a finer and more uniformly distributed precipitate structure in the aluminum matrix, which contributes to the increase in hardness.